Akhlak, Ethics and Morals in View of the Verses of the Qur'an and Hadith of the Prophet Muhammad SAW - Didik Himmawan; Windy Renalda Rizky; Yelsi Alfitia Ningsih; Faiz Putrawan (Aslama: Journal of Islamic Studies, 2024)
In the view of the Prophet's hadith, morals were sent to perfect human behavior. The hadith implies the importance of good manners as a condition for perfecting faith. The Prophet emphasized the need to be pious, correct mistakes with kindness, and associate with people using good manners. The hadith also reflects that good manners can reach the level of worship and have a heavy weight in the scales of deeds. In addition, the hadiths convey that good manners can catch up with acts of worship and have a positive influence on one's rank in heaven. Conversely, bad manners can be an obstacle to achieving the pleasures of heaven. Thus, the hadith underlines the importance of developing good manners in daily life. The purpose of this research is to deepen the understanding of morals, ethics, and morals in the view of the Prophet's hadith. The research method applied is qualitative with literature study, using various literature sources such as books, e-books, journals, articles, and trusted websites. The data is analyzed systematically, citing and referring to literature sources according to scientific principles. The results of the literature study show that morals are a mirror of the condition of the soul, ethics are related to the teachings of good and bad, while morals include habits and behavior. In the view of the Prophet's hadith, good manners are prioritized and considered as the perfection of faith, with the aim of forming a moral and ethical human being.